The Role of Chromatography in the Food Industry - Spozhmai Osmani (International Journal for Research in Applied Sciences and Biotechnology, 2021)
The widespread usage of gas chromatography for food analysis makes it a value for scientific research. The typical chemical and food analysis tasks performed by Quall Expand use mostly quantitative or qualitative analysis of food constituents, poisons, pesticides, and waste chemicals. As well as the changes in food taste and packaging, and odour composition, and work with various extraction procedures such as using water and steam distillation, solvents. This review provides a general introduction to gas chromatography research and mentions the main uses of gas chromatography in food science in addition to high-performance liquid chromatography (HPLC). Trends from past and forecasted implementation practices are noted, evaluated, and possible trends in the present and possible future behavior of food industries. They predict that in food applications, which do not include the already gas chromatography, the fastest-developing research methods in the next decade would be used known as gas chromatography. The main three methods for quick gas chromatography are low-pressure gas chromatography or TOFOT gas chromatography/time-of-MS, which is only briefly defined, and the features of a gas chromatography are evaluated.